A functional polymorphism in the prodynorphin gene affects cognitive flexibility and brain activation during reversal learning. - Votinov, Mikhail; Pripfl, Jürgen; Windischberger, Christian; Moser, Ewald; Sailer, Uta; Lamm, Claus (Frontiers in Behavioral Neuroscience, 2015)
Whether the opioid system plays a role in the ability to flexibly adapt behavior is still unclear. We used fMRI to investigate the effect of a nucleotide tandem repeat (68-bp VNTR) functional polymorphism of the prodynorphin gene on cerebral activation during a reversal learning task in which participants had to flexibly adapt stimulus-response associations. Past studies suggested that alleles with 3 or 4 repeats (HH genotype) of this polymorphism are associated with higher levels of dynorphin peptides than alleles with 1 or 2 repeats (LL genotype). On the behavioral level, the HH group made more perseverative errors than the LL group. On the neural level, the HH group demonstrated less engagement of left orbitofrontal cortex (lOFC) and cortico-striatal circuitry, and lower effective connectivity of lOFC with anterior midcingulate cortex and anterior insula/ventrolateral prefrontal cortex during reversal learning and processing negative feedback. This points to a lower ability of the HH genotype to monitor or adapt to changes in reward contingencies. These findings provide first evidence that dynorphins may contribute to individual differences in reversal learning, and that considering the opioid system may shed new light on the neurochemical correlates of decision-making and behavioral regulation.